Neuronal scaffolding protein spinophilin is integral for cocaine-induced behavioral sensitization and ERK1/2 activation - Areal, Lorena B; Hamilton, Alison; Martins-Silva, Cristina; Pires, Rita G W; Ferguson, Stephen S G (Université d'Ottawa | University of Ottawa, 2019)
Abstract Spinophilin is a scaffolding protein enriched in dendritic spines with integral roles in the regulation of spine density and morphology, and the modulation of synaptic plasticity. The ability of spinophilin to alter synaptic strength appears to involve its scaffolding of key synaptic proteins, including the important structural element F-actin, AMPA/NMDA modulator protein phosphatase 1, and neuromodulatory G-protein coupled receptors, including dopamine receptor D2 and metabotropic glutamate receptor 5. Additionally, spinophilin is highly expressed in the striatum, a brain region that is fundamentally involved in reward-processing and locomotor activity which receives both glutamatergic and dopaminergic inputs. Therefore, we aimed to investigate the role of spinophilin in behavioral responses to cocaine, evaluating wild-type and spinophilin knockout mice followed by the examination of underlying molecular alterations. Although acute locomotor response was not affected, deletion of spinophilin blocked the development and expression of behavioral sensitization to cocaine while maintaining normal conditioned place preference. This behavioral alteration in spinophilin knockout mice was accompanied by attenuated c-Fos and ∆FosB expression following cocaine administration and blunted cocaine-induced phosphorylation of ERK1/2 in the striatum, with no change in other relevant signaling molecules. Therefore, we suggest spinophilin fulfills an essential role in cocaine-induced behavioral sensitization, likely via ERK1/2 phosphorylation and induction of c-Fos and ∆FosB in the striatum, a mechanism that may underlie specific processes in cocaine addiction.